A Role for Protein Kinase Bβ/Akt2 in Insulin-Stimulated GLUT4 Translocation in Adipocytes - Hill, Michelle M. (American Society for Microbiology, 1999)
Insulin stimulates glucose uptake into muscle and fat cells by promoting the translocation of glucose transporter 4 (GLUT4) to the cell surface. Phosphatidylinositide 3-kinase (PI3K) has been implicated in this process. However, the involvement of protein kinase B (PKB)/Akt, a downstream target of PI3K in regulation of GLUT4 translocation, has been controversial. Here we report that microinjection of a PKB substrate peptide or an antibody to PKB inhibited insulin-stimulated GLUT4 translocation to the plasma membrane by 66 or 56%, respectively. We further examined the activation of PKB isoforms following treatment of cells with insulin or platelet-derived growth factor (PDGF) and found that PKBβ is preferentially expressed in both rat and 3T3-L1 adipocytes, whereas PKBα expression is down-regulated in 3T3-L1 adipocytes. A switch in growth factor response was also observed when 3T3-L1 fibroblasts were differentiated into adipocytes. While PDGF was more efficacious than insulin in stimulating PKB phosphorylation in fibroblasts, PDGF did not stimulate PKBβ phosphorylation to any significant extent in adipocytes, as assessed by several methods. Moreover, insulin, but not PDGF, stimulated the translocation of PKBβ to the plasma membrane and high-density microsome fractions of 3T3-L1 adipocytes. These results support a role for PKBβ in insulin-stimulated glucose transport in adipocytes.